Water as a relational being in Xishuangbanna: presence, scarcity and management - Zhen Ma (European Bulletin of Himalayan Research)
Water is more than a natural resource in Dai communities in Xishuangbanna (Sipsongpanna) Dai Autonomous Prefecture of Yunnan Province, China. It is a relational being embodying both worldly and transcendental values among Dai people. Water is the critical source of irrigation for Dai people’s wet-rice cultivation and has been an important component of their Theravada Buddhist ritual practices since ancient times. However, over the past seventy years, the intensive expansion of rubber plantations, continual deforestation and large-scale diversion of rivers have led to water shortage crises in many Dai villages. Against this backdrop, this article investigates how Dai people relate to water and the challenges that water management poses for relatively low-value but water-intensive wet-rice cultivation. In recounting the stories of the Dai people, the article sheds light on the broader issue of how adaptation to a growing water crisis has shaped and will continue to shape everyday life, religious practices and politics among rice-cultivating people.